BEBERAPA FAKTOR YANG BERPENGARUH TERHADAP MOTIVASI BELAJAR MAHASISWA PERGURUAN TINGGI SWASTA (PTS) (STUDI KASUS PADA MAHASISWA FAKULTAS EKONOMI DI KOTA PALEMBANG) - Novianty, Dwi Eka; Junaidi, Junaidi (Fakultas Ekonomi Universitas IBA, 2017)
This study aims to determine the effect of student conditions, skills of lecturers teachingand campus environment on student learning motivation Faculty Economics of PTS. Thedata were collected from August - September 2017. The data used were secondary datafrom questionnaires distributed to several PTS campuses in Palembang, PalembangUniversity, Tridinanti University, IBA University and Muhammadiyah University ofPalembang. There were 260 questionnaires distributed, from which the questionnairewas then tabulated, then the statistical test using SPSS obtained the following results: 1)The result of multiple linear analysis showed that all independent variables (studentcondition, teaching skill of lecturer and campus environment) had significant influence tostudent's learning motivation, student condition variable have more dominant influencethan other variable, 2) result of t test indicate that partially variable of student conditionand campus environment have significant effect to student's motivation variable, whilepartial teaching skill has no significant effect to student's learning motivation 3) F TestResult indicate that student condition variable, teaching skill of lecturer and campusenvironment simultaneously / simultaneously have an effect on student's motivationvariable, 4) Adjusted R R Test Result are showing the coefficient of determination equalto 0,307 or 30,7% variable of student condition, teaching skill of lecturer and campusenvironment influence student learning motivation.